Drug-Induced Granulomatous Interstitial Nephritis in a Patient With Ankylosing Spondylitis During Therapy With Adalimumab - Korsten, Peter (2010)
Tumor necrosis factor α (TNF-α) inhibitors are used in the treatment of rheumatoid arthritis, psoriasis, psoriatic arthritis, Crohn disease, ankylosing spondylitis, and juvenile idiopathic arthritis. Use of TNF inhibitors is associated with the induction of autoimmunity (systemic lupus erythematosus, vasculitis, psoriasis, and sarcoidosis/sarcoid-like granulomas). We report a case of interstitial granulomatous nephritis in a patient with ankylosing spondylitis after 18 months of treatment with adalimumab. Previously reported cases of sarcoid-like reactions secondary to the use of TNF-α inhibitors involved the liver, lung, lymph nodes, central nervous system, and skin. Granulomatous nephritis after adalimumab treatment has not been described. Close observation of patients undergoing treatment with TNF inhibitors for evolving signs and symptoms of autoimmunity is required. Organ involvement is unpredictable, which makes correct diagnosis and management extremely challenging.